Exploration of numeracy in digital cultural content - Nuraini, Ni Luh Sakinah; Cholifah, Puri Selfi; Permata, Santy Dinar; Aurelia, Davina; Nabilla, Silva; Huzaimah, Cempa (Educational Challenges, 2025)
The PISA results of 2022 awarded Indonesian students poor scores in literacy and numeracy. Previous studies have suggested that numeracy skills can be improved by applying game-based learning to ethnomathematics. Therefore, a similar strategy was explored, in the form of digital content based Culturally Responsive Teaching (CRT). Purpose. This study aims to develop digital content for numeracy learning based on culturally responsive teaching, in order to present numeracy through the introduction of a cultural perspective that is valid, practical, and effective for elementary school students. Methodology. The research method was the ADDIE development model, whose acronym refers to the five stages it encompasses: analysis, design, development, implementation, and evaluation. In this research paper, validation from media experts and teachers was used, and student response questionnaires were employed to calculate scores. Results. The results show that the CRT-based digital content numeracy flipbook for elementary school students presents a reasonably good outcome in terms of validity and appeal. This media is suitable for supporting teachers in navigating numeracy learning in elementary schools. Conclusions. The digital content flipbook can support elementary school students in numeracy. Based on the result of data analysis from the development research, it can be concluded that this e-book is an effective tool in the numeracy learning process for elementary school students. Based on the validity and practical test, this e-book is classified as ‘interesting and effective’ based on criteria such as visual design, students’ questionnaires, and teachers’ assessments. The criteria were visual display, ease of use, language, implementation, and the Culturally Responsive Teaching learning model.